Civil Society Participation in Public Policy Processes in Brazilian Tourism: The Itupararanga-Sorocabana Touristic Region Forum - Araujo, Cíntia Möller (Anais Brasileiros de Estudos Turísticos, 2014)
In Brazil, since the enactment of the Federal Constitution of 1988, we have been witnessing the institutionalization of new mechanisms for political participation. Thus a variety of Councils of public policies arose and spread, in several spheres of Government and in the most varied sectors. These allowed possibilities of increasing the number of players with power to intervene in public administration and public policies. This article is intended to evaluate the democratizing nature of these forums within the field of tourism public administration, via the analysis of one experiment going on at the State of São Paulo, namely: “Itupararanga-Sorocabana Touristic Region Forum”. Actually, the research question this paper tries to answer is: to what extend do these bodies contribute to effectively built a more pluralistic public policy process in the tourism sector, thereby integrating in the debate of public policies, a variety of players representing a diversity of touristic interests.We relied on a qualitative approach (case study) and concluded that although we have been experiencing an expansion of the participation of civil society in public policy processes, there remains the challenge regarding the inclusion of some segments traditionally excluded from decision-making arenas